Penerapan Metode Berdongeng Untuk Meningkatkan Nilai- Nilai Agama Anak Usia Dini di PAUD Aisyah Desa Pajar Tinggi Kecamatan Pajar Bulan - Anggraini, Nur Aziza; Maryanto, Muhamad Agus (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to instill the effectiveness of the storytelling method in increasing the religious values ​​of early childhood development in Aisyah PAUD, Pajar Tinggi Village, Pajar Bulan District, Lahat Regency. This research uses classroom action research methods. This research design uses the Kemmis and Mc model. Taggart. This research was carried out in the even semester of the 2023/2024 academic year. The primary data source is Aisyah PAUD students consisting of 25 students, 12 boys and 13 girls. Data collection techniques use observation, interviews and documentation. The data analysis technique uses quantitative data analysis with descriptive statistics. The results of the research showed an increase in students' religious values, namely in cycle I it was 68% (Developing According to Expectations), then in cycle II it increased to 80% (Developing Very Well). This means an increase of 12%. Thus, the storytelling method has proven to be effective in increasing the religious values ​​of early childhood at Aisyah PAUD.